Methodology of redesigning a Delta-type parallel robot 3-DOF in terms of a prescribed workspace - Balmaceda Santamaría, Albert Lester; Castillo Castañeda, Eduardo (Nexo Revista Científica, 2013)
This paper develops and applies a methodology for re-designing a Delta-type parallel mechanism based on a prescribed workspace, for whatever geometric shape. The methodology was implemented in Matlab® software without using an objective function, selecting feasible minimum values of the design variables, these lengths are: fixed and mobile platform, links or arms that comprising the kinematic chain and a distance between the base fixed and space requirement. The geometric shape defined prescribed volume was compared with the shape of two workspace Delta-type robots available in the international market. The methodology was applied to parallel robot Delta-type Parallix LKF-2040, created in CICATA – IPN, Queretaro, Mexico, in order to design their industrial version. DOI: http://dx.doi.org/10.5377/nexo.v26i1.853